(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Rainfall is one of the significant element of climate. It controls various climatic processes which are directly or indirectly effects on environment. This research work engrossed on the rainfall dynamicity and concentration over Latur district. The district has been located on the south east border fringe area of Maharashtra state. The rainfall data for 41 years has been gathered from Indian Meteorological Department, Pune, Hydrological Project Department, Nashik and Socio-economic abstract of Latur districts. The distribution and its discrepancy is inspected for 10 stations. The stations have been selected based on their equal spatial location in the study region. The numerous statistical measures have been applied to assess the rainfall distribution and its variation like arithmetic mean, standard deviation, coefficient of variation, PCI etc. The mean minimum is ranges from 0.3 mm over Takali and Ahemadpur to 16.4 mm at Taka. The mean maximum rainfall during this period is observed between 54.4 mm to 113.4 mm at Takali and Ausa respectively. The SD of rainfall varies 9.9 to 23.3 at Kasarshirsi and Ausa and CV is 245.1 at Takali to 384.7 % at Wadhona. The nature of rainfall concentration is seen as moderate over Ahemadpur, Ausa, Rohina and Wadhona whereas irregular concentration over Jawala bk., Nitur, Taka, Takali and Udgir and Kasarshirsi is strongly irregular.